A STUDY ON THE ENGLISH BORROWING AT THE SPORT COLUMN IN TEMPO WEEKLY MAGAZINE - Ahmad Hanan; Kamarudin Kamarudin; Lalu Suratman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2018)
This research is aimed to find out the types and process of borrowing words and frictions in the borrowing word from English into Indonesian language in Sport column of Tempo weekly magazine. The writer uses descriptive qualitative method and describes one by one the borrowing words from English. Then the writer analyzes those words, which are experienced the change of meaning, such as in Extension, Narrowing, and equal in meaning. And also the writer analyzes the type, such as loanword and loanblend. To support the analysis, the writer uses some dictionaries, such as Merriam Webster Dictionaryand Kamus KataSerapan Asing dalam Bahasa Indonesia and other related references. As the conclusion, the writer found the borrowing words from English into Indonesia. The writer concludes there are types of borrowing words process such as loanwords and loan blend. In addition, the process that presented in this research is the changes of meaning such as extension, narrowing, and same in meaning. But the writer didn’t find regeneration and degeneration process in those borrowing words.